Identification of somatostatin receptor subtypes 1, 2A, 3, and 5 in neuroendocrine tumours with subtype specific antibodies. Issue 1 (1st January 2002) - Kulaksiz, H; Eissele, R; Rössler, D; Schulz, S; Höllt, V; Cetin, Y; Arnold, R
Abstract : Background and aims: Recently, novel somatostatin receptor (sstr) subtype specific ligand analogues have been developed for medical treatment of neuroendocrine tumours expressing different sstrs (sstr1–5). At present, individual expression patterns of sstr subtypes are based on methods such as in situ hybridisation and polymerase chain reaction at the transcriptional level. Therefore, we generated subtype specific antibodies against sstr1, 2A, 3, and 5 and analysed their presence, cellular localisation, distribution, and expression pattern in 33 gastrinomas, 36 insulinomas, and 35 tumours associated with a carcinoid syndrome by immunohistochemistry at the translational level. Methods: Western blotting experiments were performed in the normal human pancreas used as a reference organ and in tumour tissues; at the cellular level, sstrs were localised by immunohistochemistry in tissue paraffin sections. Results: In western blot analyses, the antibodies identified the respective receptors in their correct molecular range in extracts of the pancreas and neuroendocrine tumours. Using immunohistochemistry and immunofluorescence, the antibodies specifically detected the receptors in islet cells of the normal pancreas. Immunohistochemistry in the tumours revealed that all investigated sstr subtypes were highly expressed in the different tumour types. The frequency and expression pattern of the individual sstr subtypes varied considerably not only between the different tumour types but also in each patient. Conclusions: We conclude that immunohistochemistry with subtype specific antibodies can be used in clinical routine work to analyse sstr expression patterns for each patient before treatment and to facilitate well directed individual medical therapy by administering subtype specific somatostatin analogues.